2020
DOI: 10.1021/acs.macromol.0c00638
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Emission-Active Chiral Helical Polymers Show Strong Circularly Polarized Luminescence in Thin Films

Abstract: Circularly polarized luminescence (CPL) materials with aggregation-induced emission (AIE) performance have attracted extensive attention. In this study, we successfully achieve CPL emissions in chiral helical substituted polyacetylenes with tetraphenylethene (TPE) pendants. The polymers are constructed by copolymerization of an achiral TPE-containing acetylenic monomer with a chiral monomer. The obtained polymer exhibits unique state-dependent CPL behavior. More specifically, the polymer is CPLsilent in a disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 66 publications
1
53
0
2
Order By: Relevance
“…The presence of helical chirality in polymer backbones facilitates the polymers to show intense CPL with the highest g lum of +0.136 and -0.264. Following the same idea, Zhao and Deng et al [64] further achieved CPLs in chiral helical substituted polyacetylenes bearing TPE pendants. More recently, the same group [119] reported pyrene-functionalized chiral helical polyacetylenes, in which handedness inversion and amplification of CPL were simultaneously realized in helical polymer systems.…”
Section: Constructing Cpl-active Polymers Via Covalently Bondingmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of helical chirality in polymer backbones facilitates the polymers to show intense CPL with the highest g lum of +0.136 and -0.264. Following the same idea, Zhao and Deng et al [64] further achieved CPLs in chiral helical substituted polyacetylenes bearing TPE pendants. More recently, the same group [119] reported pyrene-functionalized chiral helical polyacetylenes, in which handedness inversion and amplification of CPL were simultaneously realized in helical polymer systems.…”
Section: Constructing Cpl-active Polymers Via Covalently Bondingmentioning
confidence: 98%
“…to prepare CPL-active polymers [4,64,65], metal-organic frameworks (MOFs) [66], and thermally-activated delayed fluorescence (TADF) [67] materials, which will be further discussed in the following sections (Sections 2.5, 2.6, and 3.2).…”
Section: Cpl From Aie-active Aggregatesmentioning
confidence: 99%
“…This kind of intensified Cotton effects have been frequently reported in literature dealing with chiral polymers, possibly attributed to the ordered arrangement of chiral polymer chains in solid film state. [12,50,52] Besides, CD and UV-vis absorption of the prepared film (R-P9/1 3/3 /PMMA film as a representative) under different rotation angles were also characterized (Figure S11, Supporting Information). According to the CD data, it could be found that the CD signal of the film hardly changes with the rotation of test angel, suggesting that the optical activity of the film is originated from circular polarity rather than linear dichroism and birefringence.…”
Section: And Cpl Performance Of Copolymers Prepared From Hsscpmentioning
confidence: 99%
“…Circularly polarized luminescence (CPL) materials have attracted ever-increasing attention for their great potential applications in a wide variety of areas such as information storage, 3D optical displays, optoelectronic devices, etc. [1][2][3][4][5][6] Up to date, the main building blocks for constructing CPL materials include rare earth complex, [7] organic small molecules, [8,9] chiral polymers, [10][11][12] supramolecular self-assemblies, [13][14][15][16] and liquid crystals. [17,18] Of particular interest, chiral helical polymers have been widely used DOI: 10.1002/marc.202200111 to prepare CPL-active materials with high luminescence dissymmetry factor (g lum ) values due to their unique helical structure and chiral amplification effect.…”
Section: Introductionmentioning
confidence: 99%
“…[15] To date, many emerging CPL-active materials, including lanthanide metal complexes, organic molecules, natural macromolecules, synthetic polymers, self-assembly systems, and chiral liquid crystals (LCs), have been reported. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In terms of practical application, the development of an appropriate CPL material with a high degree of polarization has become urgent. [36,37] Nevertheless, it is difficult for most CPL materials to provide high asymmetry factors to meet the needs of some optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%